Maritime Economic Geopolitics and Risk Transmission: A Systematic Literature Review of the Impact of U.S.-Iran Tensions on International Trade Flows in Indonesian Waters - Anwar T; Muhammad Sahid; Amrin Amrin; Muhammad Ilham (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Geopolitical tensions in the Persian Gulf, particularly between Iran and the United States, constitute a systemic risk factor for global maritime trade. However, their cascading implications for sea lanes of communication (SLOCs) in Southeast Asia, especially Indonesian waters, remain insufficiently examined in the international academic literature. Objective: This study aims to examine how Iran–United States tensions in the Persian Gulf function as a systemic disruptive variable within the global maritime security architecture and how their implications for SLOCs in Indonesian waters remain analytically underrepresented. Methods: This study conducted a PRISMA-compliant systematic literature review of 30 peer-reviewed articles published between 2002 and 2025, selected from the Scopus database using predefined inclusion criteria related to maritime security, energy geopolitics, and strategic chokepoints in the Persian Gulf and Southeast Asia. The review was supplemented by VOSviewer keyword co-occurrence bibliometric analysis to map thematic clusters and identify structural gaps in the literature. Results: The findings identified three principal risk transmission mechanisms: energy supply volatility through the Strait of Hormuz, tanker rerouting dynamics through Indonesian straits, and intensifying great-power naval rivalry in the region. Keyword co-occurrence analysis quantitatively confirmed the absence of strong conceptual linkages between the Persian Gulf geopolitics cluster and the Indonesian maritime security cluster in the global literature. Conclusion: This study affirms the urgency of reorienting international maritime security discourse to position Indonesia as an active geostrategic actor rather than a passive recipient of regional conflict dynamics.